Research The Endurance Tensile Strength of Polychloroprene-Phenolic Resin-Methyl Methacrylate Adhesive Polyblend in Acid Condition - Yani Kartika Pertiwi (Biopropal Industri, 2011)
Adhesive polyblend polychloroprene-phenolic resin grafted with methyl methacrylate, best grafted composition due to tensile strength result will be tested the endurance of tensile strength in acid condition. The goal of this research is for knowing endurance of tensile strength after sunk in acetic acid solution with variation of sink time. Tensile strength analysis results showed that adhesive degradation was started after 56 hours. FT-IR spectogram showed C=C bond of polychloroprene which is the back bone structure of graft copolymer not founded in ~1600 cm-1 that indicated adhesive polyblend degradated caused by polyblend and acetic acid reaction.